Study on the axial compression behavior of RC columns strengthened with cementitious grout. (1st June 2023) - Peng, Gang; Hu, Xiaopeng; Niu, Ditao; Zhang, Yong; Zhong, Shuai
Highlights: Compression behavior of RC columns strengthened with cementitious grout were studied. The failure modes, compression capacity, displacement, and strain were analyzed. Effects of replacement positions, thickness on compression behavior were discussed. Calculation methods of compression capacity were proposed and verified. Abstract: The axial compression behavior of reinforced concrete (RC) columns strengthened with cementitious grout was studied by conducting the axial compressive tests on twelve column specimens. The effects of replacement position and thickness on the failure modes, load–displacement responses, compression capacity, and load–strain curves of the columns were discussed. The results indicated that interfacial cracks were not observed at the interface between the cementitious grout and concrete. The strengthened columns gained peak load enhancements of 10.8–61.0%, while the corresponding displacement increased to a lesser extent and even reduced (−16.8–44.9%). Comparisons of axial compression performance of the strengthened specimens with the same replacement ratio but different replacement positions indicated that the strengthening effects of specimens with different replacement positions listed in descending order was: four side replacement, opposite replacement, adjacent replacement, and unilateral replacement. Moreover, the increase of the compression capacity of strengthened columns increased obviously with an increase in the strength of the cementitious grout and replacement ratio, while decreased with an increase in the strength of concrete. The axial strain of the concrete side was larger than that of the cementitious grout side during the loading process for unsymmetrically strengthened columns with cementitious grout, and the specimen exhibited physical eccentricity. Thereafter, an equivalent compression constitutive model of the composite section of RC columns strengthened with cementitious grout was proposed based on the established compression constitutive models of concrete and cementitious grout. A calculation method for the axial compression capacity of existing RC columns strengthened with cementitious grout was proposed considering the lateral restraint effect of stirrups on concrete and cementitious grout, and reduction of capacity caused by physical eccentricity of specimens. A comparison between the calculated and experimental results demonstrated that the results obtained by the proposed method were in good agreement with that of the experimental results.